KONSELING INDIVIDU DAN KONSELING KELOMPOK DENGAN TEKNIK SELF-CONTROL DALAM MENGURANGI PERILAKU MALADAPTIF SISWA DI SEKOLAH - Putri Rachmawati Wahyuni Asyri Ep; Dina Hajja Ristianti; Sumarto; Beni Azwar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Maladaptive student behavior is a problem that can hinder students' adjustment, social development, and academic success at school. One factor related to the emergence of maladaptive behavior is low self-control skills. This study aims to examine the forms of maladaptive behavior that can be addressed through self-control techniques, their application in individual and group counseling services, and their effectiveness in reducing students' maladaptive behavior. The study used a literature review method (library research) with data sources in the form of journal articles, books, and relevant research results from the period 2016–2026. Data were analyzed using content analysis techniques. The results of the study indicate that self-control techniques are used to address various maladaptive student behaviors, including online game addiction, gadget addiction, cyberloafing, bullying, aggressive behavior, off-task behavior, truancy, and alcohol consumption habits. The application of self-control techniques is carried out through the stages of self-monitoring, self-evaluation, goal setting, self-control strategies, and self-reinforcement. In both individual and group counseling, self-control techniques have been shown to effectively improve self-regulation, emotional management, impulse control, and help reduce maladaptive behaviors in students. Therefore, self-control techniques are an effective approach to supporting students' personal, social, and academic development through individual and group counseling services.